Photoshop Training As A Material For Recognition Of Past Learning In The Jember Green Nature Housing Youth Group - Wardoyo, Ari Eko; Fitriyah, Nur Qodariyah (Universitas Muhammadiyah Jember, 2024)
This service activity has a long-term goal of creating a youth group in green natural housing who have knowledge and creativity in the field of computers, especially for graphic design applications. The short term goal is to educate youth groups in using tools in graphic design applications, namely Photoshop, so that it is hoped that youth groups can design and develop the creative talents of youth groups in the field of design. This activity is carried out using a comprehensive mentoring method for the natural housing youth group through socializing graphic design applications, using the Photoshop application, creating modules for using graphic design applications with Photoshop which are used to guide the operation of the application, thus helping the youth group in the practice of making designs and it is hoped that they will be able to create brochure designs, logo designs and other designs. The final output that will be achieved from this activity is increasing the ability of youth groups in using computers as a tool for developing youth groups' creativity in the field of design. Apart from that, the youth group has a guide to using the Photoshop application to help its members use the tools and develop image designs. Scientifically, the final outcome of this service activity is the publication of the results of this service in a service journal or mass media publication.